Primary skeletal muscle cells from chronic kidney disease patients retain hallmarks of cachexia in vitro. Issue 2 (14th January 2022) - Baker, Luke A.; O'Sullivan, Thomas F.; Robinson, Katherine A.; Graham‐Brown, Matthew P.M.; Major, Rupert W.; Ashford, Robert U.; Smith, Alice C.; Philp, Andrew; Watson, Emma L.
Abstract: Background: Skeletal muscle wasting and dysfunction are common characteristics noted in people who suffer from chronic kidney disease (CKD). The mechanisms by which this occurs are complex, and although progress has been made, the key underpinning mechanisms are not yet fully elucidated. With work to date primarily conducted in nephrectomy‐based animal models, translational capacity to our patient population has been challenging. This could be overcome if rationale developing work could be conducted in human based models with greater translational capacity. This could be achieved using cells derived from patient biopsies, if they retain phenotypic traits noted in vivo . Methods: Here, we performed a systematic characterization of CKD derived muscle cells (CKD; n  = 10; age: 54.40 ± 15.53 years; eGFR: 22.25 ± 13.22 ml/min/1.73 m 2 ) in comparison with matched controls (CON; n = 10; age: 58.66 ± 14.74 years; eGFR: 85.81 ± 8.09 ml/min/1.73 m 2 ). Harvested human derived muscle cells (HDMCs) were taken through proliferative and differentiation phases and investigated in the context of myogenic progression, inflammation, protein synthesis, and protein breakdown. Follow up investigations exposed HDMC myotubes from each donor type to 0, 0.4, and 100 nM of IGF‐1 in order to investigate any differences in anabolic resistance. Results: Harvested human derived muscle cells isolated from CKD patients displayed higher rates of protein degradation ( P  = 0.044) alongside elevated expression of both TRIM63 (2.28‐fold higher, P  = 0.054) and fbox32 (6.4‐fold higher, P  < 0.001) in comparison with CONs. No differences were noted in rates of protein synthesis under basal conditions ( P  > 0.05); however, CKD derived cells displayed a significant degree of anabolic resistance in response to IGF‐1 stimulation (both doses) in comparison with matched CONs (0.4 nm: P  < 0.001; 100 nM: P  < 0.001). Conclusions: In summary, we report for the first time that HDMCs isolated from people suffering from CKD display key hallmarks of the well documented in vivo phenotype. Not only do these findings provide further mechanistic insight into CKD specific cachexia, but they also demonstrate this is a reliable and suitable model in which to perform targeted experiments to begin to develop novel therapeutic strategies targeting the CKD associated decline in skeletal muscle mass and function.